Relationship between individual and country-level socio-economic background, USMLE step scores, and demographics of international medical graduates and residency match results - Daria D. Hunter; Ronna L. Campbell; Aidan F. Mullan; Joel R. Anderson; James L. Homme (BMC Medical Education, 2024)
Abstract Purpose Twenty five percent of practicing physicians in the US are International Medical Graduates (IMGs) – physicians who completed their medical school training outside of the United States and Canada. There are multiple studies demonstrating higher socio-economic background is associated with medical school matriculation in the US. However, despite a substantial prevalence of IMGs in the American healthcare system, studies of the association between demographics, socio-economic background, and securing a residency position in the match are lacking. Methods We created a survey with questions on residency match-related data and information on personal socio-economic background. An invitation to participate in the study was sent to all IMGs that applied to the included residency programs after the conclusion of the 2022 residency match. We used multivariable logistic regression to compare survey responses to the odds of securing a residency match. Results The total number of survey respondents was 744 (response rate 15.1%). We found that younger age, higher United States Medical License Examination (USMLE) scores, higher-income country of origin (including the United States), fewer match attempts, applying to fewer specialties, having parents with college degree or higher, and coming from higher-than-average or lower-than-average family income were independently associated with increased odds of matching. Gender, personal income, and visa status did not demonstrate significant associations with residency match. Conclusions Residency match is a significant expense for IMGs, especially for those from lower-income countries. International applicants from higher socio-economic backgrounds might have advantages in securing medical residency positions in the United States when controlling for other variables.